Ammonia transport is independent of PNH3 gradients across the gastrointestinal epithelia of the rainbow trout: A role for the stomach. Issue 2 (11th November 2022) - Jung, Ellen H.; Nguyen, Jessica; Nelson, Charlotte; Brauner, Colin J.; Wood, Chris M.
Abstract: Although the gastrointestinal tract (GIT) is an important site for nitrogen metabolism in teleosts, the mechanisms of ammonia absorption and transport remain to be elucidated. Both protein catabolism in the lumen and the metabolism of the GIT tissues produce ammonia which, in part, enters the portal blood through the anterior region of the GIT. The present study examined the possible roles of different GIT sections of rainbow trout ( Oncorhynchus mykiss ) in transporting ammonia in its unionized gas form—NH3 —by changing the PNH3 gradient across GIT epithelia using in vitro gut sac preparations. We also surveyed messenger RNA expression patterns of three of the identified Rh proteins ( Rhbg, Rhcg1, and  Rhcg2 ) as potential NH3 transporters and NKCC as a potential ammonium ion (NH4 + ) transporter along the GIT of rainbow trout. We found that ammonia absorption is not dependent on the PNH3 gradient despite expression of Rhbg and Rhcg2 in the intestinal tissues, and Rhcg2 in the stomach. We detected no expression of Rhbg in the stomach and no expression of Rhcg1 in any GIT tissues. There was also a lack of correlation between ammonia transport and [NH4 + ] gradient despite NKCC expression in all GIT tissues. Regardless of PNH3 gradients, the stomach showed the greatest absorption and net tissue consumption of ammonia. Overall, our findings suggest nitrogen metabolism zonation of GIT, with stomach serving as an important site for the absorption, handling and transport of ammonia that is independent of the PNH3 gradient. Abstract : We highlight the nitrogen metabolism zonation of the rainbow trout gastrointestinal tract, where luminal ammonia absorption is not dependent on the NH3 gradient across the intestinal epithelium despite expression of potential NH3 transporters, yet the stomach showed the greatest absorption and net tissue consumption of ammonia independent of the NH3 gradient. Research Highlights: Rainbow trout gastrointestinal tract (GIT) ammonia absorption is not dependent on the PNH3 gradient despite expression of Rh and NKCC . Stomach showed the greatest ammonia absorption and net tissue consumption, independent of the PNH3 gradient.